THE INFLUENCE OF DIGITAL TRANSFORMATION, ORGANIZATIONAL CULTURE, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEE ENGAGEMENT AT BANK SUMUT HEAD OFFICE - Prianatama, Reza; Edward, Yusuf Ronny; Lubis, Fajar Rezeki Ananda; Simanjuntak, Dahnil Anzar (SULTANIST: Jurnal Manajemen dan Keuangan, 2026)
This study aims to analyze the influence of digital transformation, organizational culture, and job satisfaction on employee performance through employee engagement as a mediating variable at Bank Sumut Head Office. The research uses a quantitative approach with an explanatory research design. The population consists of 516 employees. Data were collected using a Likert-scale questionnaire, and analyzed using analyzed using the measurement model (outer model), Goodness of Fit (GoF) criteria, and the structural model (inner model). The results indicate that digital transformation, organizational culture, and job satisfaction have a positive and significant effect on employee engagement. Furthermore, employee engagement has a significant positive impact on employee performance. Employee engagement also serves as a mediating variable in the relationship between digital transformation, organizational culture, and job satisfaction on employee performance. These findings highlight the crucial role of employee engagement in enhancing employee performance, particularly in the context of digital transformation and organizational culture development within the banking sector. Therefore, Bank Sumut’s management is encouraged to strengthen digital transformation initiatives, foster a positive organizational culture, and improve job satisfaction in order to boost employee engagement and optimize performance.